(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Insufficient physical activity (PA) is a growing global health problem: nearly one-third (31%) of adults worldwide did not meet recommended PA levels in 2022, compared with 23% in the year 2000. WHO has provided recommendations for both individual-level PA (Guidelines on PA and sedentary behaviour) and PA promotion (Global Action Plan for PA). Their importance for the national level is manifold: They set targets for PA practice within different population sub-groups, provide monitoring indicators, and assist stakeholders from policy and practice in promoting PA within the population. However, the adoption of WHO’s recommendations at national level varies between countries and over time, depending on a variety of factors such as overall country capacity, current population PA levels, and the status of national PA strategy deployment. This symposium presents the development or update of national PA recommendations in three European countries that are in various stages of their national PA policy cycle: Switzerland, Germany, and Hungary. The symposium will start with Switzerland, focusing on the experience and challenges of updating the national PA recommendations based on the WHO PA guidelines. The second and third presentations will introduce the update of the German recommendations for PA and PA promotion, looking at: (1) the integration of different settings, health equity, and planetary health, and (2) ways to better include qualitative aspects of PA, like exercise in green spaces or activities with meaningful others. The final presentation will showcase the importance of using the Hungarian PA recommendations for the monitoring of the national Active Lifestyle Strategy. The presentations will be followed by a moderated discussion of topics such as: (1) links between updates of WHO and national PA recommendations, (2) the implementation of national PA recommendations and policies, or (3) the limits of PA recommendations in positively impacting population-level PA.